Tinjauan literatur bahaya ergonomi pada industri pembuatan tahu di Indonesia - Lestari, Wiji; Syahadat, Ray March; Zulfa, Nely (Jounal of Enviromental Science Sustainable, 2023)
Ergonomics hazard in the tofu industry has not been specifically discussed. The purpose of this article is to provide a literature review related to ergonomic hazards in the tofu industry in Indonesia. Ten articles in the last five years relevant to the topic of tofu industrial hazard ergonomics were obtained from Google Scholar and then analyzed. The results obtained by the literature generally discuss hazards in this industry in general without distinguishing between physical, chemical, biological, and ergonomic hazards. There are 28 body points that are often complained about in the tofu industry. There are three main things needed to ensure occupational safety and health related to ergonomic hazards in the tofu industry. These three things include a physical approach, education, and the provision of first aid facilities for occupational safety and health in the tofu industry.